Aging- and injury-related differential apoptotic response in the dentate gyrus of the hippocampus in rats following brain trauma - Sun, Dong; McGinn, Melissa; Hankins, Jeanette; Mays, Katherine; Rolfe, Andrew; Colello, Raymond (Frontiers in Aging Neuroscience, 2013)
The elderly are among the most vulnerable to traumatic brain injury (TBI) with poor functional outcomes and impaired cognitive recovery. Of the pathological changes that occur following TBI, apoptosis is an important contributor to the secondary insults and subsequent morbidity associated with TBI. The current study investigated age-related differences in the apoptotic response to injury, which may represent a mechanistic underpinning of the heightened vulnerability of the aged brain to TBI. This study compared the degree of TBI-induced apoptotic response and changes of several apoptosis-related proteins in the hippocampal dentate gyrus (DG) of juvenile and aged animals following injury. Juvenile (p28) and aged rats (24 months) were subjected to a moderate fluid percussive injury or sham injury and sacrificed at 2 days post-injury. One group of rats in both ages was sacrificed and brain sections were processed for TUNEL and immunofluorescent labeling to assess the level of apoptosis and to identify cell types which undergo apoptosis. Another group of animals was subjected to proteomic analysis, whereby proteins from the ipsilateral DG were extracted and subjected to 2D-gel electrophoresis and mass spectrometry analysis. Histological studies revealed age- and injury-related differences in the number of TUNEL-labeled cells in the DG. In sham animals, juveniles displayed a higher number of TUNEL+ apoptotic cells located primarily in the subgranular zone of the DG as compared to the aged brain. These apoptotic cells expressed the early neuronal marker PSA-NCAM, suggestive of newly generated immature neurons. In contrast, aged rats had a significantly higher number of TUNEL+ cells following TBI than injured juveniles, which were NeuN-positive mature neurons located predominantly in the granule cell layer. Fluorescent triple labeling revealed that microglial cells were closely associated to the apoptotic cells. In concert with these cellular changes, proteomic s